Integrating Reliability in Systems Engineering Management. Issue 3 (3rd July 2019) - Sols, Alberto; Salado, Alejandro
Abstract: Understanding how engineering disciplines, activities, and artifacts are connected between them is key to success as an engineering manager. However, engineering managers are often unaware of these relationships in the area of reliability engineering. This results in omitting necessary reliability activities, incorrectly executing them, and/or executing them at the wrong time. This paper discusses how reliability activities effectively integrate in the system's life cycle, enabling engineering managers to understand what has to be done, when and why, from a reliability point of view. We contend that this understanding facilitates communication between systems engineers and reliability experts. Eight real cases are presented to show the negative consequences of managing engineering projects without a systemic understanding of reliability. Based on such experience, a number of recommendations are given for engineering managers.